2018
DOI: 10.1136/bmjsrh-2018-200098
|View full text |Cite
|
Sign up to set email alerts
|

Predicting poor compliance with follow-up and intrauterine contraception services after medical termination of pregnancy

Abstract: NCT01223521;Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Fertility resumes rapidly after pregnancy regardless of outcome. If contraception is left until a follow‐up appointment (which many women fail to attend) many women are already at potential risk of pregnancy and those choosing LARC methods often face further delays accessing trained providers.…”
Section: Methodsmentioning
confidence: 99%
“…Fertility resumes rapidly after pregnancy regardless of outcome. If contraception is left until a follow‐up appointment (which many women fail to attend) many women are already at potential risk of pregnancy and those choosing LARC methods often face further delays accessing trained providers.…”
Section: Methodsmentioning
confidence: 99%
“…In an RCT from Finland, the post abortion IUD placement rate was 91% for placement at the abortion clinic, compared with only 24% for primary healthcare placement 27 . Non‐attendance has been associated with a history of previous pregnancy and abortion, 28 whereas we could not identify any predictors for attendance. It is noteworthy that, in our study, all women who chose an IUD based on recommendation from the healthcare provider attended the placement visit.…”
Section: Discussionmentioning
confidence: 61%
“…Both of these prospective studies had attendance rates >85% with follow-up at the abortion clinic. 15,16 In contrast, the Pohjoranta et al study, 13 also performed in Finland, retrospectively found that 57% of patients attended follow-up at a primary healthcare center. These results support the positive impact of scheduled follow-ups, preferably at the abortion clinic.…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 93%
“…12 Patients who miss this follow-up visit risk being left without contraception. 13 Previous trials have examined the effectiveness and safety of IUD placement after medical abortion within 1 week of mifepristone administration or at a later time point. 14,15 However, these trials have been performed with an ultrasound examination before IUD placement as part of the protocol.…”
Section: Introductionmentioning
confidence: 99%